Similarity search and applications : 11th International Conference, SISAP 2018, Lima, Peru, October 7-9, 2018, Proceedings /: 11th International Conference, SISAP 2018, Lima, Peru, October 7-9, 2018, Proceedings. (2018) - Unknown
No abstract available